Qualitative assessment of the Irish 2018 Wellbeing Framework in education - Caoimhe Dempsey; Selina MacCoy (The Economic and Social Research Institute (ESRI), 2024)
Recent evidence shows increasing wellbeing and mental health difficulties among young people in Ireland (Carroll et al., 2024) and internationally (WHO, 2021). This evidence emerges against the backdrop of significant policy focus, with the Department of Education publishing the Wellbeing Policy Statement and Framework for Practice in 2018 aiming to improve wellbeing initiatives in Irish primary and post-primary schools. This paper presents a qualitative analysis of stakeholder perspectives on the objectives and implementation of the policy. A theoretical sampling framework was applied, and semi-structured interviews conducted with diverse voices within the system including policy makers in the department of education; specialist educational service providers; school leaders and teachers; students; parents and academics. Results indicate that stakeholders were positive about the benefit of having a framework for future directions and decisions. However, several stakeholders reiterated the same challenge in translating the policy into effective school practices, often underpinned by a lack of teacher professional development and competing demands on resources. The policy has faced particular challenges due to the pandemic, which has created a need for reflections on the future shape of the policy. Including the voice of stakeholders, particularly students, will be critical in supporting effective development of the policy.
Keywords: 330; Schüler; Zufriedenheit; Psychische Krankheit; Bildungsreform; Irland